2018
DOI: 10.1007/s11914-018-0463-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Approach to Bone Metastases

Abstract: The more common use of targeted chemotherapies and focused high-dose radiation have altered the treatment paradigm of bone metastases. Overall changes in the surgical treatment of bone metastases have been driven by an increased multidisciplinary approach to metastatic cancer and the awareness that one type of surgery does not work for all patients. The individual patient treatment goals dictate the surgical procedures used to achieve these goals. Advancements in adjuvant therapy-like radiation and more target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The advent of computer-aided surgical navigation systems helped greatly in reducing radiation exposure, but many hospitals have yet to equip them because of their high cost. Siegel et al [2018] (25) found that the radiation time during percutaneous pedicle screw fixation was longer than in the conventional open surgery group. The effective dose in the transcutaneous group was more than three times that in the open group.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of computer-aided surgical navigation systems helped greatly in reducing radiation exposure, but many hospitals have yet to equip them because of their high cost. Siegel et al [2018] (25) found that the radiation time during percutaneous pedicle screw fixation was longer than in the conventional open surgery group. The effective dose in the transcutaneous group was more than three times that in the open group.…”
Section: Discussionmentioning
confidence: 99%
“…Dose fractionation schedules included multi-fraction radiation, such as 30 Gy in ten fractions. Adjuvant therapy-like radiation [19] was used after surgery or POP to prevent tumor recurrence.…”
Section: Management Algorithmmentioning
confidence: 99%
“…Readily available morphology-based scoring tools for predicting pathologic long bone fracture have limited accuracy [35] , [36] . Nonetheless, a review by Siegel et al points out that the presence of pain with weight bearing is likely the most important factor in determining risk for pathologic fracture [37] . Extent of cortical involvement and osteolytic lesions have also been shown to be associated with higher risk of pathologic fracture [38] , [39] .…”
Section: Resultsmentioning
confidence: 99%